EateryTag: investigating unobtrusive edible tags using digital food fabrication - Miyatake, Yamato; Punpongsanon, Parinya (Frontiers in Nutrition, 2025)
Human-Food Interaction (HFI) examines how digital integration can enhance dining experiences, with food tagging playing a crucial role in connecting physical dining environments with digital information. Attaching optical tags to the surface or sides of food often detracts from its aesthetics, negatively impacting the perceived taste and overall dining experience. To address this issue, we propose an unobtrusive food tagging approach that embeds tags inside the food, maintaining both its visual appeal and sensory qualities. We first developed a tagging method using a 3D printer and proposed an end-to-end pipeline for embedding and retrieving the tags. We evaluated this method in terms of tag detectability, concealability, and the eating experience. Additionally, we developed tagging methods using molding and stamping to extend acceptability to the traditional cooking environment. Through a workshop with three home chefs, we found that these methods are accessible and easy to adopt for novice users. Our findings demonstrate the potential of embedded food tagging to integrate digital information into the dining experience without compromising culinary integrity. This approach offers new directions for HFI research and practical applications.